Comparison of Concentration- and Homology-Dependent Effects of the Proinflammatory Cytokine Interleukin-1β (IL-1β) in a Bovine Chondrocyte Inflammation Model - Robert Ossendorff; Sarah Kurth; Su Wang; Max Jaenisch; Elio Assaf; Sebastian Scheidt; Kristian Welle; Christof Burger; Dieter C. Wirtz; Andreas C. Strauss; Frank A. Schildberg (Cells)
Inflammation models with the proinflammatory cytokine interleukin-1β (IL-1β) are widely used in the in vitro investigation of new therapeutic approaches for osteoarthritis (OA). The aim of this study was to systematically analyze the influence of IL-1β in a 3D chondral pellet culture model. Bovine articular chondrocytes were cultured to passage 3 and then placed in pellet culture. Titration of IL-1β (100–0.1 ng/mL) was performed with both human and bovine recombinant protein in chondrocyte culture for 2 weeks. Gene expression of anabolic (collagen 2, aggrecan, cartilage oligomeric protein (COMP), proteoglycan-4 (PRG-4)), catabolic matrix metallo proteinases (MMP-3, MMP-13), dedifferentiation (collagen 1) markers and inflammatory cytokines IL-6 and IL-8 was determined. Analysis of the cell culture medium was performed for the inflammatory markers IL-6 and nitric oxide (NO). In general, the influence of IL-1β was shown by a decrease in the expression of anabolic markers (collagen 2, aggrecan, PRG-4), whereas the catabolic markers MMP-3 and MMP-13 as well as the inflammatory markers IL-6 and IL-8 were significantly increased. This was observed both at the early time point (day 4) and at the late time point (day 14). The described inflammatory effects were confirmed by increased concentration-dependent release of NO and IL-6. The threshold concentration for a detectable effect compared to control differed between groups, but was reached earlier by homologous application of IL-1β. This study provides a systematic evaluation of IL-1β-specific effects on chondrocytes in a 3D pellet culture model, which is highly relevant for comparisons of studies in OA-specific drug development.